Socio-demographic and Clinical Characteristics of Patient with Thyroid Cancer - Hossain, AKM Farhad; Siddiqui, Md Mahmudur Rahman; Khatun, Sayada Fatema (Anwer Khan Modern Medical College Journal, 2020)
Background: Thyroid cancer is the most common malignant disease in endocrine system. It is an emerging public health issue associated with burden on the family, community and the nation. The aim of this study is to determine the socio-demographic and clinical characteristics of patient with thyroid cancer attending in tertiary hospital. Methods: This cross sectional study was conducted among 246 thyroid cancer patients in two tertiary hospitals of Dhaka city from 01 July 2018 to 30 June 2019. The subjects were selected purposively following specific selection criteria and maintaining ethical issues. Data were collected by face to face interview using a semi-structured questionnaire and checklist. Data were analyzed by the statistical package for the social science (SPSS) version 23. Results: This study revealed that majority (74.4%) of respondents was female, married (72%), housewife (61.4%), rural respondent (41.1%) and had primary education (69%). Mean (± SD) age of the respondent was 37.85(±12.20) years (Range 14-70 years) and mean (± SD) monthly family income was Tk. 17681(±10602). Out of 246 cases, 204 (82.9%) was papillary and 42 (17.1%) was follicular carcinoma. Various clinical presentations included visible neck swelling in 225 (91.5%), swollen lymph node in 103 (41.9%), pain 90 (36.6%), Difficulties in swallowing 87 (35.4%), Hoarseness of voice in 141 (57.3%), cough along with swelling 47(19.1%), Difficulties in breathing due to swelling in 13(5.3%) of the patients. Conclusion: Incidence of thyroid cancer has increased worldwide specially in female patients in 3rd and 4th decades of life. As thyroid cancer is a growing public health problem in Bangladesh, proper screening and early diagnostic facilities at all level should be available to measure its actual burden in the country. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 54-58